Erratum: Blind deconvolution in model-based iterative reconstruction for CT using a normalized sparsity measure (Physics in Medicine and Biology (2019) 64 (215010) DOI: 10.1088/1361-6560/ab489e) - Hehn, Lorenz; Tilley, Steven; Pfeiffer, Franz; Stayman, J. Webster (Physics in Medicine and Biology, 2020)
Publishing errors in figures 3–6 were made, which were not present in the proof. While the figures are referenced correctly in the text and the captions are correct, the content of the figures (images, diagrams, etc) are interchanged. As a consequence, the captions do not relate to the content of the figures. Specifically, the content of figure 3 is found in figure 6, the content of figure 4 is shown in figure 3, the content of figure 5 is depicted in figure 4 and the content of figure 6 is found in figure 5. The corrected figures are shown in the following.
CRIS-Team Scopus Importer:2023-03-08